Knowledge, practice and attitude towards standard isolation precautions in nurses, auxiliary nurses and midwives of Shahid Sadoughi hospital Yazd, Iran - Mohammadzadeh, Mahmoud; Behnaz, Fatemah; Parsa, Shirin (International Journal of Infection Control, 2013)
Objective of this study was to evaluate knowledge, Practice and Attitude of nurses, auxiliary nurses and midwifery staff towards standard isolation precautions.In a cross sectional survey 200 nurses, auxiliary nurses and midwifery staff, were evaluated by a questionnaire for knowledge of, attitude and practice towards standard isolation precautions at a teaching hospital in Yazd, Iran. The data was collected and analyzed by using SPSS14 software.Two hundreds (87%) of 230 nurses, auxiliary nurses and midwives responded the distributed questionnaires. Knowledge and attitudes were moderate but their practice was relatively poor. Mean score of knowledge, attitude and practice towards standard isolation precautions were 11.9(Maximum=16.5), 27(Maximum=50), 4.6(Maximum=9) respectively. Practice scores of women were significantly higher than men (P value 0.028). Knowledge score of study subjects increased significantly with age (pvalue0.004).A positive linear correlation was observed between knowledge and practice (p value 0.01 correlation coefficient 0.173). This study revealed that knowledge and Attitudes towards standard isolation precautions were moderate but their practice was relatively poor. Serious defects in knowledge of health care workers regarding hand hygiene, disinfecting endoscopes, avoiding recapping needles and respiratory isolation precautions were present. An educational program on standard isolation precautions for all health care workers can improve the infection control by increasing compliance of them with standard isolation precautions that is necessary for care of patients.